ANALYSIS OF SOLID AND HOLLOW SHAFT USING MOD-GOODMAN METHOD (Comprehensive Journal of Science, 2025)
Power shafts are the most crucial components of a machine, and they are frequently subject to fatiguedue to variable external loads. The goal of this research is to design solid and hollow shafts with constant loadand torque in order to anticipate the percentage reduction in shaft mass and change in diameter. The modifiedGoodman approach was used to calculate the shaft's diameter, which was then compared to the maximum shearstress method. The results show that hollow shafts have a 28% lower mass than solid shafts with the samematerial and strength, while hollow shafts have a 5% higher outer diameter. When using maximu
Keywords: Power Shaft, Hollow Shaft, Solid Shaft, Mod_Goodman Method, Fatigu